A Novel k-out-of-n Oblivious Transfer Protocol from Bilinear Pairing. (18th April 2012) - Chou, Jue-Sam
Abstract : Oblivious transfer (OT) protocols mainly contain three categories: 1-out-of-2 OT, 1-out-of- n OT, and k -out-of- n OT. In most cases, they are treated as cryptographic primitives and are usually executed without consideration of possible attacks that might frequently occur in an open network, such as an impersonation, replaying, or man-in-the-middle attack. Therefore, when used in certain applications, such as mental poker games and fair contract signings, some extra mechanisms must be combined to ensure the security of the protocol. However, after a combination, we found that very few of the resulting schemes are efficient enough in terms of communicational cost, which is a significant concern for generic commercial transactions. Therefore, we propose a novel k -out-of- n oblivious transfer protocol based on bilinear pairing, which not only satisfies the requirements of a k -out-of- n OT protocol, but also provides mutual authentication to resist malicious attacks. Meanwhile, it is efficient in terms of communication cost.